On the Relation between the Open‐Circuit Voltage and Quasi‐Fermi Level Splitting in Efficient Perovskite Solar Cells. Issue 33 (25th July 2019) - Caprioglio, Pietro; Stolterfoht, Martin; Wolff, Christian M.; Unold, Thomas; Rech, Bernd; Albrecht, Steve; Neher, Dieter
Abstract: Today's perovskite solar cells (PSCs) are limited mainly by their open‐circuit voltage ( V OC ) due to nonradiative recombination. Therefore, a comprehensive understanding of the relevant recombination pathways is needed. Here, intensity‐dependent measurements of the quasi‐Fermi level splitting (QFLS) and of the V OC on the very same devices, including pin‐type PSCs with efficiencies above 20%, are performed. It is found that the QFLS in the perovskite lies significantly below its radiative limit for all intensities but also that the V OC is generally lower than the QFLS, violating one main assumption of the Shockley‐Queisser theory. This has far‐reaching implications for the applicability of some well‐established techniques, which use the V OC as a measure of the carrier densities in the absorber. By performing drift‐diffusion simulations, the intensity dependence of the QFLS, the QFLS‐ V OC offset and the ideality factor are consistently explained by trap‐assisted recombination and energetic misalignment at the interfaces. Additionally, it is found that the saturation of the V OC at high intensities is caused by insufficient contact selectivity while heating effects are of minor importance. It is concluded that the analysis of the V OC does not provide reliable conclusions of the recombination pathways and that the knowledge of the QFLS ‐V OC relation is of great importance. Abstract : The lack of selectivity and energy alignment of the charge transport layers in perovskite solar cells induce a mismatch between the external open‐circuit voltage and the internal quasi‐Fermi level splitting due to enhanced interface recombination. This limits the maximum open‐circuit voltage potentially achievable and results in its saturation at high illumination intensities.